2017
DOI: 10.1016/j.jss.2017.03.060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypothermia on splenic leukocyte modulation and survival duration in severely septic rats

Abstract: Background Therapeutic hypothermia in severe septic shock is associated with prolonged survival. We hypothesized that moderate hypothermia would prolong survival and modulate the inflammatory response in rats with septic shock by exerting its therapeutic effect on splenic leukocytes. Materials and Methods Severe septic shock was created in rats by cecal ligation and incision (CLI). One hour after CLI or laparotomy, rats were randomized to sham, normothermia (NT), or 4 hours of hypothermia (HT) followed by 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…35 We found that pUS of the spleen abrogated proinflammatory cytokine production and the exodus of splenic leukocytes into circulation in the early phases after CLI. Consistent with prior studies, 14 CLI induced significant contraction in splenic weight of the control animals, suggesting a migration of reservoir splenic leukocytes into the circulation, an effect that was not mitigated by abdominal washout. However, after pUS treatment, splenic contraction while still present was appreciably attenuated, and corresponding peripheral leukocyte counts were reduced to a level similar to septic animals that had undergone splenectomy (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…35 We found that pUS of the spleen abrogated proinflammatory cytokine production and the exodus of splenic leukocytes into circulation in the early phases after CLI. Consistent with prior studies, 14 CLI induced significant contraction in splenic weight of the control animals, suggesting a migration of reservoir splenic leukocytes into the circulation, an effect that was not mitigated by abdominal washout. However, after pUS treatment, splenic contraction while still present was appreciably attenuated, and corresponding peripheral leukocyte counts were reduced to a level similar to septic animals that had undergone splenectomy (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, as anticipated, this only delayed the development of fatal multiorgan failure due to intraabdominal sepsis and did not prevent mortality within 24 h. Simultaneous splenectomy performed at the time of surgical washout further prolonged the survival of the rats after CLI, supporting the theory that the spleen is a significant contributor to the acute inflammatory responses that account for much of the morbidity and mortality associated with septic shock. 14 In its immunoregulatory role, the spleen is the primary source of TNF-a production and acts as a reservoir for most of the body's phagocytic cells. 20 There are limited published studies on the role of the spleen in sepsis, and human clinical data that compare the outcomes of asplenic to normal patients in sepsis are not present in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But a critical analysis of the literature reveals that the link between spleen and TNF production is far from firmly established. The chief piece of evidence linking spleen and TNF is that splenectomy drastically impairs the rise of TNF in the plasma of animals with systemic inflammation induced by bacterial lipopolysaccharide (LPS) or cecal perforation (9)(10)(11). This fact, however, does not necessarily imply that the spleen is the main source of circulating TNF, because it does not rule out the possibility that splenectomy could render other TNF-producing organs less responsive to inflammatory stimuli.…”
Section: Introductionmentioning
confidence: 99%